Status of Pesticide Use in Vegetables in Kaski, Nepal - Baral R., Sudikshya; Gyawali , Kiran (International Journal of Social Sciences and Management, 2025)
This study was conducted in Kaski district among 100 commercial vegetable farmers using a pretested interview schedule to access the pesticides used, respondent's knowledge, health hazards experienced and safety measures on use of pesticides. MS Excel and SPSS were used to analyze the data. Insecticides, fungicides and neem-based herbal pesticides were majorly used in vegetables while agro-vets were the major source of information to the farmers. Majority of the farmers were aware about the trade names, color label, banned pesticides, waiting period and effect of misuse of pesticides while only a minority of them were aware about the working mode of action of pesticides. About 40% farmers reported health issues on use of pesticides; major symptoms experienced were dizziness and skin irritation. Majority of farmers only used mask and gloves during application of pesticides. It was found that a majority 52% farmers were categorically spending less on pesticides while pesticide use was found to be a determining factor of income in vegetable farms. Int. J. Soc. Sc. Manage. Vol. 12, Issue-1: 38-45.